Da norma á forma: urbanismo contemporâneo e a materialização da cidade / From norm to form: contemporary urbanism and the materialization of the city - Barbosa, Eliana Rosa de Queiroz (2016)
This thesis discusses the rela ons between form and norm in the materializa on of the ci es and the pragma c contemporary urbanism, in its most commonly discussed mode: the urban project. The urban project is here understood as the media ng elements of urban transforma on, which today lack theoriza on and instrumentali es in the Brazilian context. Through the dialec c rela on between theore cal discourse and empirical observa on, the materializa on of the contemporary city is discussed, by means of the conceptual fi gures Defi ni on, Induc on, and Improvisa on, which relate to processes triggered by regula ons. The fl oodplain of Tietê, between Lapa and Barra Funda, located in the west region of the city, between the river and the rail, is used as an empiric object, a site which generated the theore cal refl ec ons and was evaluated as in its historic materializa on as in its contemporary redevelopment. The work off ers a spa al historiography of the site´s materializa on, by means of the elabora on of conceptual formal fi gures, which guided the historic materializa on process, and evaluates the contemporary materializa on, guided by the urbanis c instrument Urban Opera on, conceived to promote urban projects in the city. Depar ng from the thesis that there is no urbanis c instrument that places the project and urban design as the media ng and ar cula ng element in the Brazilian public policy on urban development today, yet some level of design, or defi ni ons that design involves, is necessary, avoiding predatory processes in the city´s materializa on. Contemporary urban projects have to incorporate urban design strategies in its concep on in order to materialize according to socially agreed goals. Thus, the present research discusses the contemporary role of the urban project and urban design in the materializa on of São Paulo.